Evaluation of three mechanisms of action (SGLT2 inhibitors, GLP-1 receptor agonists, and sulfonylureas) in treating type 2 diabetes with heart failure: a systematic review and network meta-analysis of RCTs - Gao, Huize; Wei, Qian; Zou, Anqi; Yu, Keying; Song, Da; Li, Jian; Han, Huize; Liu, Aidong (Frontiers in Endocrinology, 2025)
ObjectiveWe aimed to evaluate and compare the efficacy and safety of three antidiabetic drug classes—SGLT2 inhibitors, GLP-1 receptor agonists, and sulfonylureas—in patients with type 2 diabetes mellitus (T2DM) complicated by heart failure (HF). We focused on their differential effects on both cardiovascular outcomes (e.g., heart failure biomarkers and cardiac function) and metabolic outcomes (e.g., glycemic control and body weight), aiming to determine whether the newer agents offer superior cardiometabolic benefits. A network meta-analysis was conducted to integrate available evidence and compare all interventions simultaneously.MethodsA comprehensive literature search was performed in PubMed, EMBASE, and the Cochrane Library. encompassing all available records up to December 10, 2024. Fourteen RCTs were included. A Bayesian network meta-analysis was utilized to integrate direct and indirect evidence, facilitating a comparative ranking of various SGLT2 inhibitors—canagliflozin (CANA), ipragliflozin (IPRA), empagliflozin (EMPA), remogliflozin (REMO), licogliflozin (LICO), and dapagliflozin (DAPA)—as well as one GLP-1 receptor agonist—semaglutide (SEMA)—and a sulfonylurea—glimepiride (GLIM)—with respect to their efficacy and safety profiles.ResultsSEMA (SMD = –0.22, 95% CI: –1.31 to 0.87) demonstrated the most favorable outcome in reducing BNP levels. LICO (SMD = –0.91, 95% CI: –1.76 to –0.06) ranked highest for body weight reduction, indicating the greatest impact. GLIM (SMD = –0.64, 95% CI: –1.12 to –0.17) showed the strongest effect on lowering HbA1c, while DAPA (SMD = 0.34, 95% CI: –0.97 to 1.65) was the top-ranked agent for improving LVEF. Safety analysis indicated that LICO and IPRA had the lowest incidence of adverse events. GLIM was associated with an increased risk of hypoglycemia, whereas DAPA was linked to a higher risk of urinary tract infections.ConclusionSEMA significantly improves both metabolic control and BNP levels, making it suitable for patients requiring comprehensive management of metabolic abnormalities and heart failure. LICO offers a distinct advantage in weight management, particularly benefiting individuals with obesity. DAPA demonstrates notable efficacy in optimizing HbA1c and LVEF, making it a preferred option for patients needing more intensive cardiac support. Despite its moderate efficacy, GLIM remains a viable choice for certain patients due to its favorable safety profile and cost-effectiveness. Collectively, these findings provide essential evidence-based insights to guide individualized therapeutic strategies in type 2 diabetes complicated by heart failure.